A Dynamic Traffic Regulation System with Dynamic Rerouting - Hammer, Peter; Hansen, Christian List; Petersen, Henrik Gordon; Philipsen, Per; Ramsgaard, Brian Kirstein; Ruhoff, Peder Thusgaard (Proceedings from the Annual Transport Conference at Aalborg University, 1997)
In this article we describe the omgoing development and analysis of DTRS: A Dynamic Traffic Regulation System with dynamic rerouting. Futhermore, we discuss the development of a cellular automata based microscopic traffic simultor which is used testing and validating the methods and strategies of DTRS.